Exploring artificial intelligence competencies for the future workforce: a systematic literature review using the PRISMA protocol - Mohd Rasdi, Roziah; Idris, Fahim Hafiy; Krauss, Steven Eric; Omar, Muhd Khaizer (Springer Nature Switzerland, 2024)
Artificial intelligence (AI) and its use is spreading throughout society and transforming traditional workplaces into digital and virtual environments. The transition is anticipated to be disruptive, with the demand for certain occupational skills declining or increasing, depending on their function. Despite the rapid growth in AI use, empirical approaches to AI competencies remain under-investigated. The current work aims to bridge this gap by conducting a complete literature review of AI competencies required for AI intervention. This systematic review was conducted in accordance with the PRISMA publication criteria. The primary database in Scopus was utilised to narrow the article range. The thematic analysis results revealed four major themes: technical competency, methodology competency, social competency, and personal competency. Twelve sub-themes highlighting the distinctiveness of human soft talents, which remain necessary even in the AI age, were developed from the four core topics. Implication for practice are also put forth.